SEMANTIC TRANSFER MECHANISMS IN THE FORMATION OF MODERN MINING TERMINOLOGY: A METONYMIC PERSPECTIVE (Eureka Journal of Language, Culture & Social Change, 2026)
Mining terminology has historically developed through semantic mechanisms that enable ordinary lexemes to acquire specialized industrial meanings. Unlike metaphor, which relies on resemblance, this study argues that metonymy – based on conceptual contiguity and associative proximity – plays the central role in restructuring vocabulary for the mining domain. By integrating cognitive-semantic theory with historical lexicology, this article investigates how everyday English words (e.g., vein, face, shaft, bed) underwent systematic metonymic transformation. The study utilizes a qualitative semantic analysis supported by a specialized corpus of mining texts to trace these shifts from medieval to contemporary discourse. Results demonstrate that miners conceptualize underground space through embodied and spatial schemas, utilizing patterns such as part-for-whole and instrument-for-action. This research contributes to terminology studies by demonstrating that technical lexicons are not merely functional labels but reflections of professional cognitive mapping.
Keywords: Metonymy, cognitive linguistics, mining terminology, embodied cognition.